2014
DOI: 10.1021/jf403860b
|View full text |Cite
|
Sign up to set email alerts
|

Holadysenterine, a Natural Herbicidal Constituent from Drechslera australiensis for Management of Rumex dentatus

Abstract: Rumex dentatus L. is a problematic weed of wheat. Bioassay-directed isolation of culture filtrates of a plant pathogenic fungus Drechslera australiensis gave holadysenterine as the main herbicidal constituent against this weed of wheat. Leaf disc bioassay showed that herbicidal activity of holadysenterine was comparable to that of synthetic herbicide 2,4-D. This is the first report of this herbicidal compound from the genus Drechslera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Javaid et al (2013) found that metabolites of various Trichoderma species prepared in M-1-D medium showed greater herbicidal activity against germination and growth of parthenium than those prepared in malt extract broth. Similar variable herbicidal activity was found in metabolites of Drechslera species prepared in different growth media against Rumex dentatus (Akbar andJavaid, 2010, 2013). Recently, Javaid et al (2017) reported that metabolites of Alternaria japonica prepared in malt extract broth and potato dextrose broth showed different herbicidal activities against parthenium.…”
Section: Laboratory Bioassayssupporting
confidence: 59%
See 1 more Smart Citation
“…Javaid et al (2013) found that metabolites of various Trichoderma species prepared in M-1-D medium showed greater herbicidal activity against germination and growth of parthenium than those prepared in malt extract broth. Similar variable herbicidal activity was found in metabolites of Drechslera species prepared in different growth media against Rumex dentatus (Akbar andJavaid, 2010, 2013). Recently, Javaid et al (2017) reported that metabolites of Alternaria japonica prepared in malt extract broth and potato dextrose broth showed different herbicidal activities against parthenium.…”
Section: Laboratory Bioassayssupporting
confidence: 59%
“…However, synthetic herbicides create environmental problems and some resistance of weeds against herbicides. Thus, in this situation there has been a need of safe and eco-friendly weedmanagement strategies (Teeraraka et al, 2010;Akbar et al, 2014). In recent years, some studies have been carried out to control parthenium and other weeds in laboratory, green houses, and under filed conditions by fungal metabolites (Javaid, 2010;Akbar and Javaid, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of these alternative approaches is the use of fungal metabolites either in crude form or as purified compounds (Javaid et al, 2013;Akbar and Javaid, 2013). There are various reports in which fungal metabolites successfully seized the growth of various weeds including parthenium (Javaid and Ali, 2011;Javaid et al, 2017), through the production of antifungal compounds namely holadysenterine (Akbar et al, 2014), drazepinone (Evidente et al, 2005), and ophiobolin A (Evidente et al, 2006). The herbicidal activity of various fungal species including Trichoderma, Dreschlera, Alternaria and Aspergillus against parthenium has been reported in previous literature Javaid, 2012, 2013;Javaid et al, 2013Javaid et al, , 2017Bashir et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…In vitro bioassays using crude fractions were performed according to the methodology adopted by Akbar et al (2014). Tender leaflets from 25 days old plants (C. album) were used for this purpose.…”
Section: In Vitro Bioassays With Crude Fractionsmentioning
confidence: 99%
“…Similarly, Phomentrioloxin is a phytotoxic compound produced by Phomopsis sp., a potential mycoherbicide for the control of Chenopodium album weed (Cimmino et al, 2013a). Akbar et al (2014) isolated and characterized an herbicidal compound, holadysenterine, from metabolites of D. australiensis. This compound caused necrosis and discoloration on leaf discs of Rumex dentatus.…”
Section: Mass Spectrometry Of the Isolated Purified Toxinmentioning
confidence: 99%